Hubungan Motivasi Berprestasi dan Harga Diri dengan Kinerja Guru SD di Malang - Fabiola Hendrati (University of Merdeka Malang, 2014)
This study examines the relationship of achievement motivation and self-esteem with the performance of primary school teachers in Malang. The results of this study indicate that between self-esteem and performance of teachers is a significant positive correlation with the yield at 6.416, p = 0.022 (p 0.05). It shows the higher the self-esteem of a teacher, the higher the performance of elementary school teachers in Malang, and conversely the lower the self-esteem, the lower the performance of primary school teachers in Malang. The results of research that achievement motivation have a relationship with the teacher's performance, it is in accordance with the theories that have been proposed which states that the presence of high motivation from both inside and outside, then the teacher will be able to improve its performance optimally. While effective contribution shows that self-esteem and achievement motivation with the same effective contribution of 40.7% of the teachers' performance, the remaining 59.3% is influenced by other factors not examined in this study.